Stochastic risk analysis and management - Harlamov, Boris, author (London, UK : ISTE, Ltd. ; Hoboken, NJ Wiley, 2017)
Mathematical Bases -- Cramér-Lundberg Model -- Models With the Premium Dependent on the Capital -- Heavy Tails -- Some Problems of Control.
The author investigates the Cramer Lundberg model, collecting the most interesting theorems and methods, which estimate probability of default for a company of insurance business. These offer different kinds of approximate values for probability of default on the base of normal and diffusion approach and some special asymptotic.
Includes bibliographical references and index.
Keywords: Risk management -- Mathematical models; Stochastic analysis